The Seats of the Mighty, Volume 4 - Parker, Gilbert, 1862-1932 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Seats of the Mighty, Volume 4" by Gilbert Parker is a historical novel likely written during the late 19th century. The story unfolds through the eyes of Captain Robert Moray, an officer caught in the tumult of the French and Indian War, as he navigates the complex political and personal conflicts associated with his captivity in Quebec. The opening of the novel introduces Captain Robert Moray as he interacts with a self-important French Governor, who holds him captive yet displays arrogance about his authority. As Moray contemplates his fate, he expresses a desire to walk upon the ramparts rather than suffer in solitude, showcasing his rebellious spirit. The narrative presents his longing for freedom and the complexities of his relationship with Alixe, the daughter of the man who will be his temporary captor. As tensions rise and the world outside stirs with impending conflict, Moray's strategic conversations with guards and allies hint at plans for an escape, setting the stage for the adventures and trials that await him in the quest for both personal freedom and honor. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Seats_of_the_Mighty
Release date is 2004-08-01
This eBook was produced by Andrew Sly
Keywords: Canada -- History -- To 1763 (New France) -- Fiction; United States -- History -- French and Indian War, 1754-1763 -- Fiction